Antibacterial properties of antimicrobial peptide HHC36 modified polyetheretherketone - Gao, Weijia; Han, Xiao; Sun, Duo; Li, Yongli; Liu, Xiaoli; Yang, Shihui; Zhou, Zhe; Qi, Yuanzheng; Jiao, Junjie; Zhao, Jinghui (Frontiers in Microbiology, 2023)
Polyetheretherketone is considered to be a novel bone defect repair material owing to its mechanical properties and biocompatibility. Because its radiolucency and elastic modulus close to that of human cortical bone, it is gradually becoming an alternative to titanium. However, its clinical application is limited due to its biological inertness and susceptibility to bacterial infection during implantation. To solve this problem, it is urgent to improve the antibacterial properties of Polyetheretherketone (PEEK) implants. In this work, we immobilized the antimicrobial peptide HHC36 onto the 3D porous structure of sulfonated PEEK by a simple solvent volatilization method. The surface morphology, chemical composition, and hydrophilicity of all materials were then evaluated by field-emission scanning electron microscopy, energy dispersive spectroscopy and contact angle measuring. The release experiment showed that the HHC36 on the surface of the sample can be continuously released for up to 10 d. The in vitro antibacterial and cytological experiments proved that the samples loaded with HHC36 had excellent antibacterial properties and good cytocompatibility. To evaluate the in vivo anti-infection performance of the samples and biocompatibility, we established a rat subcutaneous infection model. The results showed that the HHC36 significantly reduced the bacterial viability rate on the sample surface and the inflammatory response in the surrounding soft tissues. The above results indicated that we have successfully improved the antibacterial properties of PEEK using a simple modification strategy, making it a promising anti-infective orthopedic implant material.